The impact of employee delayed retirement on university performance towards job crafting and management policy in China educational institutions - Luo, Haoren; Liu, Yaoping; Run, Pharatt; Junaidi, Junaidi (Journal of Asian Scientific Research, 2025)
The objectives of this study investigate how delayed retirement influences university management policy and performance towards job crafting among employees and lecturers at China University. 751 participants were recruited for an online survey study. Structural Equation Modeling (SEM) was used to test the research hypotheses. Delayed retirement has a positive and significant effect on job crafting, allowing employees and lecturers to redefine their roles in the workplace and university management policy. It includes engaging in mentorship, seeking autonomy, and fostering reciprocity. University management policy plays an important role in mediating the relationship between predictor variables (e.g., delayed retirement and job crafting) and university management policy. Delayed retirement significantly impacts employees' job crafting, enabling them to redefine their roles in the workplace. This means that experienced workers actively design positions to fit changing demands and capabilities to advance their careers. Stakeholders such as the government and university leaders need to collaborate to enhance university performance. The results of this study contribute to human resource literature and the educational context based on self-determination theory. These findings also highlight the importance of strategic management policies in enhancing organizational performance in both private and public organizations.